Black Garlic (Allium sativum) Sebagai Terapi Adjuvan Potensial pada Kerusakan Hepar yang Diinduksi Minyak Jelantah - Putu Devie Sri Astari; Rizki Hanriko (MAJORITY, 2020)
People from the lower middle class have consume used cooking oil patterns to save costs but can cause liver damage. Used cooking oil contains free radicals which cause liver damage. Black garlic can be a liver protective because it contains high antioxidant substances that can capture free radicals and prevent oxidative reactions. Flavonoids have a role to capture free radicals to stabilize fat peroxy radicals. Flavonoids have the ability to modulate cell signaling pathways that can regulate various cell processes, for example in growth, proliferation, and apoptosis. Black garlic has hepatoprotective potential to block the effect of tert-Butyl Hydroperoxide (t-BHP) oxidant on cell death, lipid peroxidation, oxidative stress, and inflammation in rat hepatocytes and can be an excellent natural candidate in the development of adjuvant therapies and healthy food for liver protection from damage due to the consumption of used cooking oil.